Prefabricated House Development With Tetra Pak Carton Recycling Processing - Seftiyandi Kurniawan; Caesar Rai Finaldy; Gumiwang Tresnakalingga (International Journal of Research and Applied Technology (INJURATECH), 2022)
Damage to the environment due to the increasing volume of waste every day causes concern about the impact that will be caused and felt later, in addition, the need for shelter recently has increased in line with the growth of the population in Indonesia. So not a few people who do not have a decent place to live and a lot of garbage that is not recycled properly. This is nothing to worry about if it can create a system that can reduce the potential for environmental damage caused by garbage that continues to increase and can also be a solution to provide a decent place to live. Therefore, this study made a system that can process the waste into a material that can be used as a sturdy building material and does not require much cost. The novelty of this system is in the ability to provide solutions to the problem of environmental damage caused by waste that is not recycled as well as solutions for people who do not have a place to live because of the limitations of expensive costs. Prefabricated houses also mean cutting the time in house construction to be more efficient because the design components of the house have been made outside the construction site, the material components are then brought to the construction site to be arranged modularly. According to statistics from the Brazilian government of Curitiba, waste consists mostly of organic materials, wood, glass, and fabric, and 31.7% of it can be recycled. Therefore, there is an opportunity to use these materials in developing and applying them to building construction. In addition, the cost tends to be lower when compared to conventional construction materials.